FORGIVENESS TERHADAP PERSELINGKUHAN DEMI KEBERLANGSUNGAN PENDIDIKAN ANAK - Syaiful Syaiful (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2022)
Forgiveness is the attitude of someone who is hurt not to take revenge for the perpetrator, on the contrary, there is a desire to make peace and do good even though the performer has done hurtful behavior. The goal of this study was to find out the description of forgiveness for infidelity by a partner and the factors underlying the provision of forgiveness to a partner who committed infidelity. This study uses a qualitative approach with the type of phenomenological research. The subjects in this study were six people with details of three husbands and three wives who were both victims and had children. The results of the study showed that even though the partner had committed an affair, the victim still gave forgiveness. The supporting factors for giving forgiveness are; 1) Situational factors, the victim feels bored with the situation that occurs due to the infidelity committed by the partner. 2) The relational factor, there is a direct apology from the performer to the victim. 3) Personality factors (religion), forgiving, patience, sincerity, and considering the incident of infidelity are temptations that must be faced. In addition to these three factors, there is a more basic factor in providing forgiveness by victims to the performer, namely is a responsibility for the continuity of children's education. Children will be displaced if their parents' divorce, on that basis the victim gives forgiveness to the performer who committed the affair.